“If I could read your mind…”: parental mentalizing in mothers with borderline personality disorder - Zitzmann, Jana; Georg, Anna; Rosenbach, Charlotte; Renneberg, Babette (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Individuals with a borderline personality disorder (BPD) show impairments in their ability to mentalize. Particularly in the parent-child relationship, mentalizing is an important foundation for sensitive parenting and the quality of interactive behavior. Previous studies of parental mentalizing in mothers with BPD are scarce and have focused primarily on one aspect of the multidimensional construct. In addition, there is currently no research comparing different mental disorders on different aspects of parental mentalizing, leaving disorder-specific differences unclear. Aim of this study is to examine disorder-specific differences in reflective functioning and mind-mindedness, two facets of parental mentalizing.